1967
DOI: 10.1029/jz072i021p05485
|View full text |Cite
|
Sign up to set email alerts
|

Riometer quiet day curves

Abstract: This paper presents a direct method of obtaining a riometer quiet day curve of the correct shape. The method is simple, and the only input information required is the early morning riometer readings. The corrected curve is shown to be necessary in studies of average ionospheric absorption levels and their diurnal, seasonal, and solar cycle variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…), São Martinho da SerraBrazil. Its operation is based on determining the Quiet Day Curve (QDC), which methodology has been discussed extensively for several authors (Mitra and Shain, 1953;Lusignan, 1960;Fredriksen and Dyce, 1960;Steiger and Warwick, 1961;Heisler and Hower, 1967;Armstrong et al, 1977;Krishnaswamy et al, 1985;Tanaka et al, 2007).…”
Section: Instrumentation E Methodsmentioning
confidence: 99%
“…), São Martinho da SerraBrazil. Its operation is based on determining the Quiet Day Curve (QDC), which methodology has been discussed extensively for several authors (Mitra and Shain, 1953;Lusignan, 1960;Fredriksen and Dyce, 1960;Steiger and Warwick, 1961;Heisler and Hower, 1967;Armstrong et al, 1977;Krishnaswamy et al, 1985;Tanaka et al, 2007).…”
Section: Instrumentation E Methodsmentioning
confidence: 99%
“…It has been found that CNA is measured relative to the baseline of cosmic noise signal level received under quiet ionospheric conditions, which makes it important to obtain a reliable quiet day curve (QDC). As riometers have been widely used in observation of ionospheric absorption, there have been some methodology studies of the QDC generation [14][15][16][17]. However, despite lots of work done on this subject, an agreement on the methodology of the QDC generation is still out of reach.…”
Section: Introductionmentioning
confidence: 99%
“…The highest “reliable” value for a given sidereal time interval would then be a point on the QDC. Some researchers, for example Heisler and Howler [1967], Lusignan [1960] and Mitra and Shain [1953], however questioned the accuracy of the QDC derived in this way as the minimum attenuation on undisturbed days does not necessarily return to zero and is subjected to a seasonal variation.…”
Section: Introductionmentioning
confidence: 99%